Micropulse Transscleral Cyclophotocoagulation in Non-Incisional Eyes with Ocular Hypertension and Primary Open-Angle Glaucoma - Murtaza F; Kaba Q; Somani S; Tam ES; Yuen D (Clinical Ophthalmology, 2024)
Fahmeeda Murtaza,1 Qayim Kaba,2 Sohel Somani,3– 5 Eric S Tam,3– 5 Darana Yuen3,4 1Temerty Faculty of Medicine, University of Toronto, Toronto, ON, Canada; 2Cardiff University, Cardiff, Wales, UK; 3Department of Ophthalmology and Vision Sciences, University of Toronto, Toronto, ON, Canada; 4Uptown Eye Specialists, Brampton, ON, Canada; 5Division of Ophthalmology, William Osler Health System, Brampton, ON, CanadaCorrespondence: Darana Yuen, Uptown Eye Specialists, 401-7900 Hurontario Street, Brampton, ON, L6Y 0P6, Canada, Tel +1 416-292-0330, Fax +1 416-292-0331, Email daranayuen2@gmail.comPurpose: To investigate the safety and effectiveness of micropulse transscleral cyclophotocoagulation (MPTSCPC) in non-incisional eyes with ocular hypertension (OHT) and early, moderate, and severe primary open-angle glaucoma (POAG).Methods: Retrospective cohort study of eyes that underwent MPTSCPC from 2016 to 2019 at an outpatient clinic in Canada. Eyes were excluded if any incisional procedures, except cataract surgery, were performed prior to MPTSCPC treatment. Laser power ranged from 900 to 2500mW.Results: A total of 153 eyes from 93 patients were included (OHT n=22; early POAG n=46; moderate POAG n=35; severe POAG n=50). The baseline IOP was 18.37 ± 4.76mmHg in the total cohort. All cohorts experienced a significant mean IOP reduction by final follow-up (total p< 0.001; OHT p=0.003; early POAG p< 0.001; moderate POAG p=0.022; severe POAG p=0.015). Overall, 52.9% of eyes achieved an IOP reduction of ≥ 20% from baseline to final follow-up (OHT 59.1%; early POAG 58.7%; moderate POAG 45.7%; severe POAG 50.0%). There was worsening in best-corrected visual acuity in the total cohort (mean difference=0.11 ± 0.36 logMAR, p=0.11), mostly attributable to cataract progression (34.1% of phakic eyes) and ocular surface disease (7.2%). The number of topical medications and drug classes remained unchanged in the total cohort (p=0.425 and p=0.791, respectively). Twenty-two eyes (14.4%) required retreatment, which provided an additional IOP reduction of 1.26mmHg (p=0.344). By final follow-up, 8 eyes (5.2%) required escalation to incisional procedures.Conclusion: MPTSCPC is a safe and effective adjunct IOP-lowering treatment in non-incisional eyes with OHT and POAG.Keywords: micropulse, cyclophotocoagulation, primary open-angle glaucoma, ocular hypertension